From Panic to Confusion to Negotiation: A Reflection from Early Response to COVID-19 in Indonesia - Setiadi, Setiadi; Lazuardi, Elan (Bina Nusantara University, 2021)
The research reflected on the response to the pandemic that emerged as it happened. It drew attention to the viral aspect of a pandemic, namely how people understood and responded to pandemics using various digital platforms. It questioned the context and reasons for what it called an immeasurable but organized community response to the COVID-19 pandemic. Digital-based research was applied through observing three mainstream digital media (Kompas TV, The Jakarta Post, and Detik.com) and social media (i.e., WhatsApp Messenger and Twitter). Data were analyzed thematically by categorizing the ways people responded to COVID-19 via social media into three thematic phases. In the first phase, digital media was used to voice frustration and disappointment with the government’s response. This had sparked public distrust of the government’s ability to deal with the pandemic at the national level. The second phase was the confusion phase. The rise of public discussion about the pandemic showed that the public was concerned about the development of the COVID-19 news in the country. The last phase was the negotiation phase. While COVID-19 was rapidly becoming a source of panic and confusion, grassroots initiatives emerged using social media. These initiatives aimed to help reduce panic and reduce socio-economic impacts. The research shows how anthropologists can still pay attention to social relations forged through social media in times of crisis where traditional anthropological fieldwork is nearly impossible. Methodologically, digital anthropology or social media ethnography is gaining momentum to be developed, considering that fieldwork cannot be done in the pandemic era.